Clinical characteristics and prognosis of immunoglobulin light chain amyloidosis patients - Song, Lijun; Su, Yan; Li, Rong; Du, Siyi; Xue, Yimiao; Gu, Yihai; Chen, Junmin; Xing, Xing; Shen, Ziyuan; Wei, Yuping (Frontiers in Medicine, 2026)
ObjectiveTo analyze the prognostic factors associated with overall survival (OS) in patients diagnosed with immunoglobulin light chain (AL) amyloidosis, with the goal of improving risk stratification and patient management.MethodsA retrospective cohort analysis was conducted on 87 patients diagnosed with AL amyloidosis at the People’s Hospital of Ningxia Hui Autonomous Region from January 2016 to December 2023. Demographic, clinical, laboratory data, and survival status were collected. Univariable and multivariable Cox regression analyses were used to identify significant predictors of OS. Kaplan–Meier survival curves and restricted cubic spline (RCS) analysis were employed to evaluate risk stratification.ResultsThe median overall survival was 22.0 months (95% CI: 15.2–28.8), and the median follow-up duration was 39.0 months (95% CI: 29.2–48.8). Our results revealed that higher bone marrow plasma cell count (BMPCs), myeloma presence, heart failure, and increased fibrinogen degradation products (FDP) were significantly associated with poor survival outcomes. The median survival time for patients with BMPCs >12% was 13 months, compared to 36 months for those with lower BMPCs. Myeloma presence was the strongest predictor of survival, with a median survival of 15 months for those with myeloma versus 36 months for those without. Multivariable analysis identified that myeloma (HR = 2.582, 95% CI: 1.105–6.034, p = 0.029), heart failure (HR = 2.258, 95% CI: 1.098–4.641, p = 0.027), higher BMPCs (HR = 1.018, 95% CI: 1.001–1.035, p = 0.035), and elevated FDP levels (HR = 1.018, 95% CI: 1.004–1.017, p = 0.001) were independent risk factors for death.ConclusionElevated BMPCs, concurrent myeloma, heart failure, and increased FDP levels were associated with poor OS of AL amyloidosis patients. These factors could be incorporated into clinical decision-making to better stratify risk and guide treatment strategies for AL amyloidosis patients.